Low-dose levobupivacaine plus fentanyl combination for spinal anesthesia in anorectal surgery - Honca,Mehtap (2015)
BACKGROUND: the aim of this study was to investigate the effects of spinal anesthesia using two different doses of fentanyl combined with low-dose levobupivacaine in anorectal surgery. METHODS: in this prospective, double-blind study, 52 American Society of Anaesthesiologists I-II patients scheduled for elective anorectal surgery were randomized into two groups. The patients in group I received intrathecal 2.5 mg hyperbaric levobupivacaine plus 12.5 µg fentanyl and in group II received intrathecal 2.5 mg hyperbaric levobupivacaine plus 25 µg fentanyl. All the patients remained in the seated position for 5 min after completion of the spinal anesthesia. Sensory block was evaluated with pin-prick test and motor block was evaluated with a modified Bromage scale. RESULTS: motor block was not observed in both of the groups. The sensory block was limited to the S2 level in group I, and S1 level in group II. None of the patients required additional analgesics during the operation. Time to two-segment regression was shorter in group I compared with group II (p < 0.01). One patient in group I and 5 patients in group II had pruritus. Hemodynamic parameters were stable during the operation in both of the groups. CONCLUSION: spinal saddle block using hyperbaric levobupivacaine with both 12.5 µg and 25 µg fentanyl provided good quality of anesthesia without motor block for anorectal surgery in the prone position.